Malic enzymes in cancer: Regulatory mechanisms, functions, and therapeutic implications - Huan Wang; Wanlin Cui; Song Yue; Xianglong Zhu; Xiaoyan Li; Lian He; Mingrong Zhang; Yan Yang; Minjie Wei; Huizhe Wu; Shuo Wang (Redox Biology, 2024)
Malic enzymes (MEs) are metabolic enzymes that catalyze the oxidation of malate to pyruvate and NAD(P)H. While researchers have well established the physiological metabolic roles of MEs in organisms, recent research has revealed a link between MEs and carcinogenesis. This review collates evidence of the molecular mechanisms by which MEs promote cancer occurrence, including transcriptional regulation, post-transcriptional regulation, post-translational protein modifications, and protein-protein interactions. Additionally, we highlight the roles of MEs in reprogramming energy metabolism, suppressing senescence, and modulating the tumor immune microenvironment. We also discuss the involvement of these enzymes in mediating tumor resistance and how the development of novel small-molecule inhibitors targeting MEs might be a good therapeutic approach. Insights through this review are expected to provide a comprehensive understanding of the intricate relationship between MEs and cancer, while facilitating future research on the potential therapeutic applications of targeting MEs in cancer management.